Analysis of Student Satisfaction as an Effort to Improve the Quality of Administrative Services for Education Personnel in Higher Education - Herlina, Herlina; Rustan, Edhy; Mahmud, Hilal (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This study aims to evaluate the level of student satisfaction with the quality of service as a step in increasing the capacity of education staff. The research method used is a quantitative survey conducted at the IAIN Palopo Campus, Faculty of Tarbiyah, and Teacher Training for six months, from March 2023 to July 2023. The population consists of active students from the class of 2020 in various study programs. Sampling was done using simple random sampling and proportionate stratified random sampling formulas, resulting in a total sample of 89 people. The instrument used is a questionnaire with 20 statements covering five indicators: tangibles, Reliability, responsiveness, Assurance, and Empathy. Each indicator is evaluated on a Likert scale, where numbers 1 to 4 indicate a rating level from less good to very good. Before the deployment of the questionnaire, validation was carried out by two validators, namely linguists and content validators. The study's results provide recommendations for improving the quality of administrative services. Data analysis uses a quantitative descriptive approach by calculating percentages. The findings showed that students positively assessed the Reliability, responsiveness, Assurance, and Empathy of education staff, with a record of potential improvements in certain aspects. This research contributes to a deep understanding of student perceptions and provides a foundation for educational institutions to improve the quality of administrative services.